2022
DOI: 10.3390/foods11111541
|View full text |Cite
|
Sign up to set email alerts
|

Reformulating Bread Using Sprouted Pseudo-cereal Grains to Enhance Its Nutritional Value and Sensorial Attributes

Abstract: Sprouting is an effective treatment for improving nutritional and bioactive properties as well as lowering the anti-nutritional compounds in pseudo-cereals. Enhancing nutritional properties when using sprouted pseudo-cereals flours as a baking ingredient requires tailored formulation. Simplex centroid designs and response surface methodology has been applied in the present study to define the ideal proportions of ternary blends of sprouted kiwicha (SKF), cañihua (SCF) and wheat flours (WF) to simultaneously en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 43 publications
4
8
0
Order By: Relevance
“…The comparative analysis of all experimental formulations revealed that the use of 100% SCF allowed reaching the highest values in most of the parameters studied (PA, TSPC and ORAC). These results agree with previous studies showing that partial replacement of refined wheat flour by sprouted kiwicha, cañihua and quinoa flours is a good strategy to fortify bread and biscuits in bioactive compounds while improving their antioxidant activity [ 31 , 32 ]. The comparison of PA values in extrudates formulated with 100% CG, SQF and SCF (Tests #1–3, Table 3 ) and their corresponding flours ( Table 2 ) revealed that the extrusion process did not influence this antinutrient in the operational conditions of this study.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The comparative analysis of all experimental formulations revealed that the use of 100% SCF allowed reaching the highest values in most of the parameters studied (PA, TSPC and ORAC). These results agree with previous studies showing that partial replacement of refined wheat flour by sprouted kiwicha, cañihua and quinoa flours is a good strategy to fortify bread and biscuits in bioactive compounds while improving their antioxidant activity [ 31 , 32 ]. The comparison of PA values in extrudates formulated with 100% CG, SQF and SCF (Tests #1–3, Table 3 ) and their corresponding flours ( Table 2 ) revealed that the extrusion process did not influence this antinutrient in the operational conditions of this study.…”
Section: Resultssupporting
confidence: 92%
“…CG showed typical nutritional composition values in accordance to previously reported data [ 29 , 30 ]. Even though there was a variation in the nutritional composition of sprouted grains that relied on genotype and germination conditions, the nutritional compositions of SQF and SCF were in accordance with previous studies [ 31 , 32 ]. The comparative analysis of the nutritional profile of SQF and SCF as compared to that of CG denoted clear differences among raw materials ( Table 2 ).…”
Section: Resultssupporting
confidence: 89%
“…Other examples can be found in the study by das Chagas et al (2021) and Paucar-Menacho et al (2022). das Chagas et al (2021) used camu-camu coproduct powders to substitute 20% of wheat flour in cookie production and reported a significant increase in the phenolic content of the produced cookies and in the antioxidant potential measured by FRAP (ferric ion reducing antioxidant power) and ORAC (oxygen radical absorbance capacity) methods (Table 1).…”
Section: Fiber Protein and Mineral Increasementioning
confidence: 94%
“…To elaborate a CF, a mixture of basic flour and other raw materials is necessary. The majority of CF studies related to production or product development do not specify the method used for CF blending, leading to the understanding that the raw materials used are mixed manually (Chikpah et al, 2020; Guardado‐Félix et al, 2020; Meenakumari et al, 2023; Olorunfemi et al, 2021; Paucar‐Menacho et al, 2022) or electric mixers are still used to blend the raw materials (Adekoyeni et al, 2018; Bora et al, 2019; das Chagas et al, 2021; Udomkun et al, 2019). In both methods, no structural or chemical interactions were observed between the raw materials.…”
Section: Elaboration Methodsmentioning
confidence: 99%
See 1 more Smart Citation